Ultra-performance liquid chromatography determination of related compounds of molindone in drug substances - Nagarajan, Balaji; Manoharan, Gunasekar; Shanmugam, Ganapathy Narayanan; Palaniyappan, Nataraj; Yarragunta, Abhinav (European Journal of Chemistry, 2022)
Effective chromatographic separation was achieved on a phenyl-hexyl stationary phase (50×2.1 mm, 1.9 micron particles) with the economical and straightforward mobile phase combination delivered in isocratic mode at a flow rate of 0.6 mL/min at 254 nm using a ultra-performance liquid chromatography (UPLC) system. In the developed method, the resolution between molindone and its related compounds was more significant than 2.0. Regression analysis shows an r2 value (correlation coefficient) greater than 0.999 for molindone and its associated compounds. This method could detect related compounds of molindone at a level below 0.009% with respect to a test concentration of 500 µg/mL for a 2.0 µL injection volume. The method has shown good, consistent recoveries for related compounds (90-110%). The test solution was found to be stable in the diluent for 48 hours. The drug was subjected to stress conditions. The mass balance was found to be close to 99.3%.